2020
DOI: 10.1038/s41598-020-79269-z
|View full text |Cite
|
Sign up to set email alerts
|

Lipid yield from the diatom Porosira glacialis is determined by solvent choice and number of extractions, independent of cell disruption

Abstract: Cell wall disruption is necessary to maximize lipid extraction yields in conventional species of mass-cultivated microalgae. This study investigated the effect of sonication, solvent choice and number of extractions on the lipid yield, lipid class composition and fatty acid composition of the diatom Porosira glacialis. For comparison, the diatom Odontella aurita and green alga Chlorella vulgaris were included in the study. Sonication effectively disrupted P. glacialis cells, but did not increase the total lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…The lipids in the diatom biomass have earlier been found to make up approximately 8-10% of the dry weight (20% of ash free dry weight) when harvested in the exponential growth phase [159,160], which is similar to the lipid content found in the present experiment where fume and compressed air solely were injected into the culture. In their review of the literature of lipid content of diatoms, Fields and Kociolek [161] reported that species cultivated in nutrient poor media contained 6.6-39.8% lipids (DW); however, their experimental data showed an average of 5.3-21.5% lipids (DW) when cultivated in nutrient replete media.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The lipids in the diatom biomass have earlier been found to make up approximately 8-10% of the dry weight (20% of ash free dry weight) when harvested in the exponential growth phase [159,160], which is similar to the lipid content found in the present experiment where fume and compressed air solely were injected into the culture. In their review of the literature of lipid content of diatoms, Fields and Kociolek [161] reported that species cultivated in nutrient poor media contained 6.6-39.8% lipids (DW); however, their experimental data showed an average of 5.3-21.5% lipids (DW) when cultivated in nutrient replete media.…”
Section: Discussionsupporting
confidence: 86%
“…The slightly higher omega-3 content, caused by the elevated 18:4n-3 content in samples with factory flue gas, was the main difference. The EPA content seems to be stable at approximately 30% no matter the cultivation conditions [46,159,160,163,164]. Other diatoms usually contain 5-20% EPA; however, species such as Skeletonema costatum and Phaeodactylum tricornutum have been reported to contain 30% of this fatty acid [165].…”
Section: Discussionmentioning
confidence: 99%
“…Before the analysis of samples, it is of great significance to select a suitable method for better compound extraction. There are some research studies about extraction-assistance treatments, , which indicate that the treatments may influence the extraction results. The treated samples were processed with triglyceride (TG) assay kits, and the optical density of GEs at 510 nm (OD 510 nm) was measured as the index of GE yield.…”
Section: Resultsmentioning
confidence: 99%
“…Lipids and pigments were extracted from lyophilized material as described in [39]. Briefly, 100 mg of material was added in 20 volumes (2 mL) of DCM/MeOH (2:1 v/v) and 5% NaCl, respectively, and centrifuged at 2000× g for 5 min before transferring the organic phase to pre-weighed 4 mL glass vials and evaporating the solvents under nitrogen.…”
Section: Lipid and Pigment Extractionmentioning
confidence: 99%